If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(3/2)*((10/9)*x+1/6)-(6*((1/4)*x+3/18))+(3/8)*x+(4/3)*x = 3*((5/12)*x-(7/18)) // - 3*((5/12)*x-(7/18))
(3/2)*((10/9)*x+1/6)-(6*((1/4)*x+3/18))-(3*((5/12)*x-(7/18)))+(3/8)*x+(4/3)*x = 0
(3/2)*((10/9)*x+1/6)-6*((1/4)*x+3/18)-3*((5/12)*x-7/18)+(3/8)*x+(4/3)*x = 0
3/2*(10/9*x+1/6)-6*(1/4*x+1/6)-3*(5/12*x-7/18)+(3*x)/8+(4*x)/3 = 0
(3/2*3*8*(10/9*x+1/6))/(3*8)+(-6*3*8*(1/4*x+1/6))/(3*8)+(-3*3*8*(5/12*x-7/18))/(3*8)+(3*3*x)/(3*8)+(4*8*x)/(3*8) = 0
3/2*3*8*(10/9*x+1/6)-6*3*8*(1/4*x+1/6)-3*3*8*(5/12*x-7/18)+3*3*x+4*8*x = 0
4*x-30*x+9*x+32*x-18+28 = 0
9*x-26*x+32*x+10 = 0
32*x-17*x+10 = 0
15*x+10 = 0
(15*x+10)/(3*8) = 0
(15*x+10)/(3*8) = 0 // * 3*8
15*x+10 = 0
15*x+10 = 0 // - 10
15*x = -10 // : 15
x = -10/15
x = -2/3
x = -2/3
| 6x-10=x-5 | | 4.8+2.3x-12=0 | | 2x=-19 | | 2x-40=11 | | 3t+4uv=44 | | 96=0.5*(x+4)*x | | 9(3)=27 | | (x/12)-4=0 | | (x-10)=26 | | -8-4x=2x+13 | | y=7.1x+8.6 | | 2x+x/3=525 | | (x/10)+8=10 | | x-1/x-2+x-3/x-4=10/3 | | (x+25)/8=5 | | 7x+52=10 | | 6.0/x=7.2 | | 93=27 | | (3x+3)/7=12 | | 7.2-4.0x=1.8 | | 20+3x=x | | 5x+80=30 | | 6(9x-5)=3 | | 8x+9=4.7x+3 | | x/3=x-2/5 | | 3x+5y+9=0 | | 2a+6b-3a^2-3b^2-6ab=0 | | 5(x/8+1)=30 | | (2x-8)/10=7 | | (6x+8)/10=8 | | (x-6)/3=6 | | (x/2)+1=20 |